Do the status and empowerment of mothers predict their daughters' reproductive outcomes? - Jessica D. Gipson; Dawn M. Upchurch (BMC, 2017)
Abstract Background Despite increased recognition of the important influences of women's status and empowerment on social and health outcomes for women and their families, there are few investigations that examine the extent to which any gains in women's empowerment may be transmitted intergenerationally, that is, between mothers and their daughters. Methods This study seeks to address this gap by using data from a unique, longitudinal, and intergenerational dataset from Cebu, Philippines (1994-2009), to examine potential influences of the status of mothers on subsequent reproductive health outcomes among their daughters. Using data from 648 mother-daughter dyads, we examine a multidimensional set of women's status and empowerment measures among the mothers to predict three outcomes among their daughters: sexual onset by 2009 (ages 25-26), use of family planning, and experience of an unintended pregnancy. Results We find that that while some of the mothers' characteristics and measures of empowerment and status were predictive of their daughters' sexual initiation, these effects were not consistent across empowerment indicators, nor were there significant effects on two of the outcomes: use of family planning or occurrence of an unintended pregnancy. Older mothers (45+ years in 1994) and mothers who were considered to be "well-kept", a locally defined measure of empowerment, were more likely to have daughters who had not engaged in sex by 2009 (ages 25-26). Daughters with higher educational levels were also more likely to delay sex, as compared to their peers. Among young women who had become sexually active, 54% reported an unintended pregnancy (mistimed or unwanted) by the age of 25-26, yet their mothers' empowerment and status were not predictive of daughters' reports of an unintended pregnancy. Conclusions Overall, these findings suggest that further research is needed to explore more proximal impacts on young women's reproductive behavior in this setting, given other related investigations on women's empowerment and its linkages to sexual debut and educational attainment in this setting. Findings from this examination of daughters' reproductive outcomes suggest that there are likely additional intervening mechanisms between onset on sexual activity and mistimed or unintended pregnancy that need further elaboration.